2015
DOI: 10.1631/jzus.b1400364
|View full text |Cite
|
Sign up to set email alerts
|

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence

Abstract: Puccinia striiformis f. sp. tritici (Pst) is the obligate biotrophic fungus responsible for stripe rust wheat. In this study, we developed and characterized 20 polymorphic microsatellite markers from the genomic sequence of an isolate of Chinese Pst race CY32. Polymorphism at each simple sequence repeat (SSR) locus was determined using 32 Pst isolates from 7 countries. The number of alleles varied from 2 to 7 across isolates, and the observed and expected heterozygosities ranged from 0.33 to 0.97 (mean 0.62) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Ninety six pairs of Pst SSR primers [32][33][34][35][36][37][38] (Table S2) were screened for useful markers. Forward primers were fluorescently 5′-labeled with either FAM, HEX, TAM or ROX.…”
Section: Ssr Primers Pcr Amplification Electrophoresis and Data Anamentioning
confidence: 99%
“…Ninety six pairs of Pst SSR primers [32][33][34][35][36][37][38] (Table S2) were screened for useful markers. Forward primers were fluorescently 5′-labeled with either FAM, HEX, TAM or ROX.…”
Section: Ssr Primers Pcr Amplification Electrophoresis and Data Anamentioning
confidence: 99%
“…Mantel test based on genetic distance with 12 SSR marker loci, and virulence distance indicated that the correlation coefficient between the virulence and the SSR marker data was low (R 2 = 0.212 to 0.370), similar to those by Chen (1993), Zhan et al (2015), and Zhan et al (2016). In those studies, virulence and molecular marker data were less significantly correlated or had low correlations.…”
Section: Discussionmentioning
confidence: 82%
“…DNA samples were diluted to 50 ng/μL for SSR amplification. Twelve pairs of published SSR primers ( 57 60 ) were used to genotype every isolate (see Table S1). The materials and specific experimental procedures described by Wang et al ( 51 ) were followed.…”
Section: Methodsmentioning
confidence: 99%